1995
DOI: 10.1038/ki.1995.161
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of cyclosporine in patients with progressive membranous nephropathy

Abstract: A controlled trial of cyclosporine in patients diagnosed with progressive membranous nephropathy (MGN) was carried out to determine whether cyclosporine (D) would be more effective than placebo (P) in reducing the rate of deterioration in renal function. Patients (N = 64) with MGN were placed on a restricted protein diet (< or = 0.9 g/kg) and followed closely for 12 months (Part 1). Patients at high risk of progression based on an absolute loss in creatinine clearance (CCr) of > or = 8 ml/min and persistent ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(106 citation statements)
references
References 30 publications
0
101
0
5
Order By: Relevance
“…The immunosuppressive recommendations for MGN based on RCTs include cyclophosphamide, chlorambucil, and cyclosporine regimens (5,18,(33)(34)(35). Most of these, but not all, concomitantly used corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive recommendations for MGN based on RCTs include cyclophosphamide, chlorambucil, and cyclosporine regimens (5,18,(33)(34)(35). Most of these, but not all, concomitantly used corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…We studied a large pooled inception cohort of patients identified at the time of biopsy diagnosis of GN and followed by prospective accrual of data from each clinic visit (10,11). For both registries, medical records were collected from the initial biopsy diagnosis or earliest available clinical presentation.…”
Section: Study Populationmentioning
confidence: 99%
“…We conducted a retrospective analysis of clinically apparent thromboembolic events in 898 patients with biopsy-proven MN diagnosed between 1969 and 2007 (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The causes of death were the development of aplastic anemia, renal failure with membranous nephropathy, liver failure associated with hepatitis B virus infection and gastric carcinoma. The relationship of CsA with the former three diseases is unclear because CsA is one of the effective treatments for aplastic anemia, 20 membranous nephropathy 21 and probably for hepatitis B virus infection as well. 22 Although immunosuppressive therapy enhances viral replication, it has been shown that CsA by itself impairs hepatitis B virus replication by blocking cytosolic calcium signaling.…”
Section: Discussionmentioning
confidence: 99%